Antihyperuricemia Effectiveness Test of Ethanol Extract of Kedondong Pagar Leaves (Lannea coromandelica (Houtt.) Merr.) Against Male White Rats (Ratus norvegicus) - Nasution, Irma Suryani; Siregar, Anggie Patrisia; Br Ginting, Astriani Natalia; Kaban, Vera Estefania; Siagian, Roy Indrianto Bangar (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Hyperuricemia is a metabolic disorder caused by elevated serum uric acid levels that may progress to gout and other complications. Although synthetic drugs such as allopurinol are effective, their long-term use may cause adverse effects, thus alternative therapies derived from natural products are needed. This study aimed to evaluate the antihyperuricemic activity of the ethanol extract of kedondong pagar leaves (Lannea coromandelica (Houtt.) Merr.) in male white rats (Rattus norvegicus). An in vivo experimental study was conducted using potassium oxonate–induced hyperuricemic rats. The animals were divided into five groups: negative control (0.5% CMC), positive control (allopurinol 10 mg/kgBW), and three treatment groups receiving the ethanol extract at doses of 100, 200, and 300 mg/kgBW. Serum uric acid levels were measured before induction, after induction, and hourly up to six hours following treatment. Phytochemical screening revealed the presence of flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides in the extract. The results demonstrated that the ethanol extract of Lannea coromandelica leaves significantly reduced serum uric acid levels in a dose-dependent manner, with the 300 mg/kgBW dose showing the greatest effect and approaching the efficacy of allopurinol. In conclusion, the ethanol extract of kedondong pagar leaves has potential as a natural antihyperuricemic agent.